A Method for Estimating Contingency Based on Project Complexity. (2015) - Touran, Ali; Liu, Jucun
Abstract: Large transportation projects have been afflicted by poor cost estimates and large cost overruns. This paper uses transit projects in the United States as an example to develop a probabilistic methodology for establishing sufficient contingency. Contingency is a reserve budget for coping with risks and uncertainties and to help keep the projects on budget. The premise of the proposed methodology is that accuracy of cost estimate is affected by project complexity. Also, this paper contends that there is an inherent underestimate in cost estimates because the estimator estimates components' costs based on the modes (most likely values) of cost distributions and then adds up these modes to arrive at total cost. In fact, the means of these cost categories have to add up to the mean of the total cost. The paper first suggests a correction for this error and then develops a methodology for establishing the level of complexity for the project, and based on these steps, develops a method for calculating an adequate contingency budget. In order to establish the contingency budget, first, a rating system is used to determine the complexity of the project. It is assumed that the more complex projects are harder to estimate accurately, and the likelihood of cost overrun is higher for these projects. Coefficient of variation is used as an indication of level of uncertainty in the cost and is assumed to be a function of complexity. The rating system scores projects according to pre-determined factors that we believe contribute to projects' complexity. Then different coefficients of variations are assigned in accordance with projects' complexity scores. It is shown that project contingency can be computed based on the coefficient of variation and the desired confidence level specified by the user. A validation is performed using a set of actual project costs.